Economic evaluation of energy saving alternatives in extractive distillation process. (4th October 2016) - Brito, K.D.; Cordeiro, G.M.; Figueirêdo, M.F.; Vasconcelos, L.G.S.; Brito, R.P.
Highlights: Analyze approaches for saving energy in extractive distillation process: optimization, thermal integration and thermal coupling. Use of a systematic procedure to find the range of all possible solutions, which includes the global optimum point of operation studied sequences. A thermally coupled extractive distillation sequence with a side rectifier did not always present the best results. In case of retrofit, it is more advantageous using the preheating of the azeotropic feed with the recycle stream of the conventional. Abstract: Until now, there has not been consensus about the superiority of thermally coupled sequence over the conventional sequence in the extractive distillation process. In this sense, the main goal of this paper is to analyze three approaches for saving energy in the extractive distillation process: optimization, thermal integration and thermal coupling. Three azeotropic mixtures were investigated: ethanol and water (M1); tetrahydrofuran and water (M2); and acetone and methanol (M3). The solvents were ethylene glycol for M1 and M2, and water for M3. The results are shown in terms of the total annual cost (TAC) and specific energy consumption (SEC), and revealed that a thermally coupled extractive distillation sequence with a side rectifier did not always present the best results. Taking the case studies from literature as a starting point (without thermal integration), the optimization procedure used in this work found that TACs are always lower. The inclusion of thermal integration in configurations led to reducing TAC for all mixtures under investigation when compared to the sequences without this integration. When comparing two modifications in the layout of extractive distillation, it can be seen that it is more advantageous to use the preheating of the azeotropic feed with the recycle stream from the recovery column of the conventional sequence than using a thermally coupled sequence.